Temperature Shift Between Vineyards Modulates Berry Phenology and Primary Metabolism in a Varietal Collection of Wine Grapevine - Gashu, Kelem; Sikron Persi, Noga; Drori, Elyashiv; Harcavi, Eran; Agam, Nurit; Bustan, Amnon; Fait, Aaron (Frontiers in Plant Science, 2020)
Global climate change and the expected increase in temperature are altering the relation between geography and grapevine (V. vinifera) varietal performance, the implication of which are yet to be fully understood. We investigated berry phenology and biochemistry of thirty cultivars, twenty red and ten white, across three seasons (2017-2019) in response to a consistent average temperature difference of 1.5oC degrees during the growing season between two experimental sites. The experiments were conducted at Ramat Negev (RN) and Ramon (MR) vineyards, located in the Negev desert, Israel. A significant interaction between vineyard location, season, and variety affected phenology and berry indices. The warmer RN site was generally associated with an advanced phenological course for the white cultivars, which reached harvest up to two weeks earlier than at MR site. They also showed stronger correlation between non-consecutive phenological stages than did red ones. In contrast, harvest time of red cultivars considerably varied according to seasons and sites. Warmer conditions extended fruit developmental phases, causing berry shriveling and cluster collapse in a few cultivars such as Pinot Noir, Ruby Cabernet and Tempranillo. Analyses of organic acid content suggested differences between red and white cultivars in the content of malate, tartrate and citrate in response to the temperature difference between sites. However, generally, cultivars at lower temperatures exhibited lower concentrations of pulp organic acids at véraison, but acid degradation until harvest was reduced, compared to the significant pace of acid decline at the warmer site. Sugars showed the greatest differences between sites in both white and red berries at véraison, but differences were seasonal dependent. At harvest, cultivars of both groups exhibited significant variation in hexose/sucrose ratio. Hexose/sucrose ratio was significantly higher among the red cultivars at the warmer RN, while this tendency was very slight among white cultivars. White cultivars seem to harbor a considerable degree of resilience due to a combination of earlier and shorter ripening phase, which avoids most of the summer heat. Taken together, our study demonstrates that the extensive genetic capacity of V. vinifera bears significant potential and plasticity to withstand the temperature increase associated with climate change.